A contemporaneidade da produção do Circo Chiarini no Brasil de 1869-1872 - Lopes, Daniel de Carvalho [UNESP] (2015)
This research has the purpose to present the trajectory of Chiarini Circus (1856 - 1897) in his first Brazilian season, 1869-1872, and analyze how the production of the circus language in the period established the various dialogues, relations, mergers and exchanges with the society, that is, how much was contemporary to this historic moment both a temporal perspective as a relational. Accordingly, by crossing a variety of sources, especially bibliographical and news, it was possible understand the dimension of artistic construction complex, business, advertising and architectural headed by circuses in the second half of the 19 th century, and how much the circus was the protagonist what was happening in terms artistic, technological, cultural and political of nineteenth-century Brazil